Análise da sustentabilidade e da competitividade da soja dos produtores do Oeste e Sudoeste do Paraná - Silva , Carlos Rogério Rodrigues da (2016)
This thesis aims to analyze the current condition of competitiveness and sustainability of soybean farmers in the West and Southwest of Paraná. The research methodology was descriptive and documentary nature, divided into an analysis of soy-related documents in Brazil, Parana and the United States, and implementation of the MAP model - Matrix of Public Policy. In the second part, was interviewed a sample represented by 42 farmers involved in soybean production and marketing processes. With a sample intentional, sectional with data collected with visits to farms. A questionnaire whose answers were analyzed by averaging Harmonic frequencies as data collection instrument was used. The results in terms of competitiveness, the MAP analysis, pointed out that soy is competitive and has room for expansion of productivity in the state, and the current profitability was achieved thanks to the bonus, represented by the difference of the internal and external exchange rate. Although it has been shown that soybean farmers have a reduction in profitability arising logistics costs and the impact represented by taxes indirectly in production. What about the interview, the social dimension showed the best results, being the most relevant to soybean producer. But as the weaknesses, the information provided shows a low level of compliance with some aspects of labor law and the non-use of protective equipment when using machinery and implements. Also a portion of the soybean farmers believe that soy did not maintain profitability over the years, despite the increase in productivity of crops in the past decade